Conceptualising the evaluation of HRIS in public sector - Hashim, Junaidah; Hj Zainuddin, Faizal; Wok, Saodah (2013)
This conceptual paper proposes a theoretical framework in examining the reaction of employees in the Malaysian public sector towards HRIS, and to examine the relationship of HRIS use with the organization performance. In Malaysia, HRIS is one of the pilot projects under the Electronic Government Flagship. Pertinent literature is reviewed and a few hypotheses are proposed.